Pengaruh Pemberian Serbuk Kulit Bawang Merah Terhadap Intensitas Serangan Meloidogyne spp. pada Tanaman Seledri - Ulfia Mawaddah Mawaddah; Elly Liestiany Liestiany; Muslimin S Sepe (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Root knot nematode attack Meloidogyne spp. is one of the main obstacles in cultivating celery (Apium graveolens L.) because it damages the root system and reduces crop yields. The use of botanical pesticides is an environmentally friendly alternative to reduce dependence on nematicides. This research aims to assess the effectiveness of shallot skin powder as a botanical pesticide in suppressing Meloidogyne spp. The experiment used a completely randomized design with five treatments including a control with powder doses (15, 20, 25 and 30 g/polybag) as well as four replications, each of which was inoculated with 500 Meloidogyne spp larvae. Attack intensity was analyzed using ANOVA and 5% BNT test. The results showed that administering shallot skin powder significantly reduced the intensity of attacks; a dose of 30 g produced the lowest attack rate of 3.30% while the control reached 63.30%. The flavonoid, saponin and alkaloid compounds in shallot skin are thought to act as nematicides. Onion skin powder has been proven to be effective and environmentally friendly as an alternative control for Meloidogyne spp. in celery cultivation.